Plate rod in humerus fracture in Caracara plancus: Challenges and outcomes of a case - J.R. Leitão; I.R. Rosado; T.T.P. Menezes; M.G. Lopes; E.G.L. Alves (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The aim of this case study was to apply a robust fixation method using the plate rod technique, which combines intramedullary pins with bone plates to provide rigid stabilization. Although commonly used in mammals, this technique has not yet been documented in avian medicine. The surgery involved detailed pre-operative evaluations and meticulous surgical planning, reflecting standards used in small animal orthopedics, to ensure that the implants were well-suited to the unique anatomical needs of the bird. In the post-operative phase, the bird was closely monitored, with follow-up radiographs showing successful implant alignment and advanced bone healing without any signs of infection. The outcome was positive, with the bird regaining full wing functionality and being released back into the wild after recovery at a wildlife rehabilitation center. This case highlights the effectiveness of the plate rod technique in managing complex fractures in avian patients, emphasizing its potential as a valuable option for similar cases, particularly in large and wild birds. The successful application and outcome of this approach provide a significant contribution to veterinary orthopedics, expanding potential methodologies for fracture treatment in avian species.